Nanotechnology‐Based Strategies for Early Diagnosis of Central Nervous System Disorders. Issue 10 (31st July 2021) - Hanif, Sumaira; Muhammad, Pir; Niu, Zheng; Ismail, Muhammad; Morsch, Marco; Zhang, Xiaoju; Li, Mingqiang; Shi, Bingyang
Abstract : Central nervous system (CNS) disorders feature the progressive and selective loss of normal brain functions. CNS disorders often include an irreversible physiological and anatomical loss of neurons that can lead to dysfunction in various parts of the brain and eventually death. Glioblastoma multiforme (GBM) and neurodegenerative diseases such as Alzheimer's disease (AD) and Parkinson's disease (PD) are hard to be diagnosed at an early stage for the prevention of disease propagation. Such diagnosis is vital for the timely commencement of actual treatments. Nanotechnology brings new diagnosis hope for CNS disorders as it provides ultrasensitive detection for more specific biomarkers. Herein, the recent progress in techniques development for detecting pathological biomarkers for GBM, AD, and PD is summarized, in particular, the principles that govern the design of these sensors, blood–brain barrier (BBB) dysfunction, and its integrity during disease development. Finally, a perspective on future directions to further advance and improve the early‐stage diagnosis of CNS disorders is presented. Abstract : Advancement of nanotechnology offers highly effective diagnostic approaches for central nervous system (CNS) diseases. Herein, valuable insights into the current status of disease markers and nanoplatform designing for applications of biosensing and bioimaging are outlined. In addition, the limitation and future opportunities for the CNS disease diagnoses are summarized.